The feeding of nations : redefining food security for the 21st century - Gibson, Mark. (Boca Raton, FL : CRC Press, 2012)
'In the last decade, the world has grown richer and produced more food than ever before. Yet in that same period, hunger has increased and 925 million remain underfed and malnourished. Exploring this troubling paradox, The Feeding of Nations: Re-Defining Food Security for the 21st Century offers a glimpse into how the simple aspiration of global food security has evolved and unfolded--with sometimes contradictory and counterproductive policies, agendas, and ideologies.'--pub. desc.
Food security: what is it? -- Good nutrition: a basic introduction -- Bad'mal'-nutrition: the physiology of hunger -- Food security: the global picture -- Sociocultural evolution -- Governance, philosophy, politics and economics -- Science, technology and philosophy -- Twentieth century: the feeding of nations--a new global enthusiasm -- The inter-war years: 1919-1939 -- World War Two: 1939-1945 -- The post-war years -- The development decade: 1960s -- Famine, oil and the food crisis: 1970s -- The lost development decade: 1980s -- The era of the conference: 1990s -- The twenty-first century: ideological convergence? -- Agriculture, forestry and fisheries -- Science and technology -- Socio-cultural -- Health and nutrition -- Environment and natural resources -- Governance, politics and economics -- Origins: aetiology and etymology--dispelling the myths -- Causality and future research -- Redefining food security -- Food for thought: discussion and considerations -- Closing remarks -- Appendices: A. Country classifications -- B. Mortality categories -- C. The Gibson framework of food security -- D. Metabolism -- E. Micronutrients -- F. Malnutrition--its assessment and measurement -- G. Biological systematics -- H. Millennium development goals -- I. Global warming--the basics -- J. Energy sources -- K. Stakeholders -- L. Conversion rates -- M. Glossary.
Includes bibliographical references and index.
Keywords: Food security; Hunger -- Prevention; Food industry and trade; Food relief; International cooperation